Curbing the practices of research misconduct: a qualitative study on the perceptions of researchers at Egyptian public institutions - Moustafa, Passant Elwy (AUC Knowledge Fountain, 2019)
Many Egyptian public academic and research institutions are facing challenges due to the rise of the practices research misconduct. These practices are data fabrication, data falsification and plagiarism. In moderately or poorly developed nations, there is a dearth of information about research misconduct. Fabrication, falsification and plagiarism are threatening the integrity of scientific research as they have become part of the research culture. Based on that, the main objectives of this study are to determine the intertwined risk factors that contribute to the occurrence of research misconduct in Egypt, and in turn, examine the perceptions and attitude of Egyptian researchers towards the practices of research misconduct. In order to fulfill these objectives, semi-structured interviews were conducted with graduate students studying in Egyptian public universities, alumni of Egyptian public universities and academic faculty members working in different Egyptian public academic or research institutions. The data analysis of the current study is most relevant to the higher education system of Egypt. The findings of the current investigation showed that although the absence of awareness is a key factor that lead to the occurrence of the practices of research misconduct in Egyptian public universities and research institutions, there are many other intertwined factors that can result in this multifaceted phenomenon. Therefore, a clear way is paved for institutions to set up mechanisms and sustainable solutions to reduce research misconduct practices in Egypt.